Analisis Struktur Gelagar Jembatan Steel Box Girder Tipe Komposit Baja-Beton: Studi Kasus : Jembatan Fly Over Jalan Alternatif Kadungora-Leles - Eko Walujodjati; Sopyan Sauri Al Qurthubi (Institut Teknologi Garut, 2023)
The Kadungora-Leles alternative road fly over bridge is the first bridge in Garut Regency to use steel box girders as its girders. Therefore, the author is interested in conducting an analysis of the steel box girder structure on this bridge. The method used in the analysis of this bridge girder structure is the Allowable Stress Design method. This analysis assumes that the stress that occurs due to the service load, which is calculated based on the elastic theory of bending beams, does not exceed the specified allowable stress. Permissible stress is determined as the ultimate strength or yield strength of steel divided by the safety factor. Bridge loading refers to SNI 1725:2016, while for analysis of bolted connections using RSNI T-03-2005. From the analysis results, it was found that the steel box girder bridge girder structure experienced a tensile stress of 1801.41 kg/cm2, experienced a deflection of 101.991 mm. After analyzing the girder connections, it was found that the bottom flange connection plate has a shear-yield capacity of 9135000 N, the web connection plate has a shear-yield capacity of 9020160 N. The bottom flange connection plate has a total of 72 bolts (24 mm) , whereas according to the analysis results only 31 bolts are needed. The bolt configuration on the web connection plate has a shear capacity of 11928.992 kN, while the shear force that must be supported is 421.933 Kn.